Morphology restrained growth of V2O5 by the oxidation of V-MXenes as a fast diffusion controlled cathode material for aqueous zinc ion batteries. Issue 47 (11th May 2020) - Narayanasamy, Mugilan; Kirubasankar, Balakrishnan; Shi, Minjie; Velayutham, Shanmuganathan; Wang, Bei; Angaiah, Subramania; Yan, Chao
Abstract : Restrained morphology and structural engineering of layered V2 O5 by the oxidation of V-MXene to form a unique V2 O5 @V2 C nanohybrids at different temperature and used as a cathode material for aqueous Zn-ion batteries (ZIBs). Abstract : Herein, we report morphology controlled growth of layered V2 O5 on V2 C by the oxidation of V-MXenes at different temperatures and used it as a cathode material for Zn-ion batteries (ZIBs). Hence, the V2 O5 nanoparticles are uniformly grown on the V2 C nanosheets with interlinked disordered carbon which provide fast diffusion and high rate performance in aqueous zinc-ion batteries.